PERCEPTIONS OF FINANCIAL RISK MANAGEMENT FOR TECHNOLOGY STARTUP COMPANIES IN THE EARLY FINANCING PHASE - Machfud; Fohan Muzakir; Maisura; Mahdawi (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze perceptions of financial risk management among technology startups in the early stages of financing. Using qualitative descriptive methods through literature review and phenomenological analysis, this study found that most startup management views financial risk management as an administrative burden in the early stages, rather than a strategic tool. However, there is a significant shift in perception after the startups pass the seed funding round, where cash flow risk management and burn rate control begin to be prioritized to maintain the company's survival. In conclusion, the integration of flexible and adaptive financial risk management is crucial from day one to mitigate the risk of early bankruptcy.